Desain RPP PBL untuk Materi Elastisitas dan Hukum Hooke Kelas XI SMA/MA - -, Juniar Afrida; Zahriah, Zahriah; Rahmati, Rahmati (Al-Khazini, 2025)
This study aims to design a Lesson Plan (RPP) based on Problem Based Learning (PBL) on the topic of elasticity and Hooke’s Law for Grade XI students of Senior High School/Madrasah Aliyah (SMA/MA). This research adopted a Research and Development (R&D) approach using the 4D development model, consisting of Define, Design, Develop, and Disseminate stages. The lesson plan was designed by integrating five PBL syntax elements into the learning activities. Validation instruments included assessment sheets filled by five content experts and three media experts. The validation results showed that the RPP obtained an average score of 88.3% from content validators and 91.75% from media validators, both categorized as "very feasible." These findings indicate that the designed RPP is of high quality and can be used as an effective instructional tool to enhance students’ active engagement in problem-solving during physics learning.